Integrating Short Conversation and English Conversation Applications to Improve Students’ Speaking Skills - Mariam, Siti; Kepirianto, Catur; Raharjo, Raharjo; Ma’mun, Nadiah (Journal of English Teaching and Learning Issues, 2022)
This study aims to explain the implementation of using short conversation and English conversation applications and also to describe student participation using this learning model. It employed a qualitative method. Classroom action research was used as the design for both cycles of the study. Planning, carrying out, monitoring, and debriefing were the four stages that make up each cycle. Participants in the study were 39 third-semester students from the Arabic education department at an Islamic university in Central Java, Indonesia, during the academic year 2022/2023. Data collection techniques used observation, pre-test and post-test. The results of this study show that there is an improvement in every cycle of students’ speaking competence using this learning model. They also are active, self-confidence and enthusiastic in joining this speaking class. It is recommended this strategy to overcome students’ difficulties in speaking English.